Donepezil as a new therapeutic potential in KCNQ2- and KCNQ3-related autism - Nissenkorn, Andreea; Bar, Lior; Ben-Bassat, Ariel; Rothstein, Lynn; Abdelrahim, Hoda; Sokol, Riki; Gabis, Lidia V.; Attali, Bernard (Frontiers in Cellular Neuroscience, 2024)
Introduction The KCNQ2/KCNQ3 genes encode the voltage-gated K channel underlying the neuronal M-current, regulating neuronal excitability. Loss-of-function (LoF) variants cause neonatal epilepsy, treatable with the M-current-opener retigabine, which is no longer marketed due to side effects. Gain-of-function (GoF) variants cause developmental encephalopathy and autism that could be amenable to M-current, but such therapies are not clinically available. In this translational project, we investigated whether donepezil, a cholinergic drug used in Alzheimer’s, suppresses M currents in vitro and improves cognitive symptoms in patients with GoF variants. Methods (1) The effect of 1 μM donepezil on the amplitude of the M-current was measured in excitatory and inhibitory neurons of mouse primary cultured hippocampal cells. M-current was measured using the standard deactivation protocol (holding at 0 mV and deactivation at −60 mV) in the voltage-clamp configuration of the whole-cell patch clamp technique. The impact of donepezil was also examined on the spontaneous firing activity of hippocampal neurons in the current-clamp configuration. (2) Four children with autism, aged 2.5–8 years, with the following GoF variants were enrolled: KCNQ2 (p. Arg144Gln) and KCNQ 3 (p.Arg227Gln, p.Arg230Cys). Patients were treated off-label with donepezil 2.5–5 mg/d for 12 months and assessed with: clinical Global Impression of Change (CGI-c), Childhood Autism Rating Scale 2 (CARS-2), Adaptive Behavior Assessment System-II (ABAS-II), and Child Development Inventory (CDI). Results (1) Application of donepezil for at least 6 min produced a significant inhibition of the M-current with an IC50 of 0.4 μM. At 1 μM, donepezil reduced by 67% the M-current density of excitatory neurons (2.4 ± 0.46 vs. 0.89 ± 0.15 pA/pF, p < 0.05*). In inhibitory neurons, application of 1 μM donepezil produced a lesser inhibition of 59% of the M-current density (1.39 ± 0.43 vs. 0.57 ± 0.21, p > 0.05). Donepezil (1 μM) potently increased by 2.6-fold the spontaneous firing frequency, which was prevented by the muscarinic receptor antagonist atropine (10 μM). (2) The CARS-2 decreased by 3.8 ± 4.9 points (p > 0.05), but in two patients with KCNQ3 variants, the improvement was over the 4.5 clinically relevant threshold. The global clinical change was also clinically significant in these patients (CGI-c = 1). The CDI increased by 65% (p < 0.05*), while the ABAS-II remained unchanged. Discussion Donepezil should be repurposed as a novel alternative treatment for GoF variants in KCNQ2/KCNQ3 encephalopathy.